Enhancing human indoor cognitive map development and wayfinding performance with immersive augmented reality-based navigation systems. (October 2021) - Zhang, Jinyue; Xia, Xiaolu; Liu, Ruiqi; Li, Nan
Abstract: Augmented reality (AR) is an interactive experience where computer-generated perceptual information is superimposed into the real-world environment. Most existing research in AR-based wayfinding has focused on the technological aspects of developing AR-based software or devices to realize navigation. No previous investigations have focused on understanding the impact of immersive augmented reality (IAR)–based systems on human wayfinding performance from the cognitive perspective. Aimed at investigating the influence of IAR-based systems on people's cognitive map development and their subsequent wayfinding performance as well as the effect of using three-dimensional (3D) layout models in IAR environments in addition to superimposed guideposts, an experiment was carried out in a building with a complex floor plan. A total of 54 university students were evenly divided into three groups: a control group with no IAR assistance, a second group using an IAR-based navigation system that includes only superimposed guideposts, and a third group using an IAR-based navigation system that includes both guideposts and a 3D layout model. Each participant was asked to conduct a spatial exploration task in the environment, sketch a floor map based on their spatial cognition, and perform a wayfinding task to find eight specific locations in the building. An analysis of the participants' performance and responses to a number of self-evaluation questionnaires collected in the experiment indicates that IAR technology can help people develop their cognitive maps more effectively and can substantially improve their wayfinding performance with a much lower workload. A second finding is that adding a 3D layout model can enhance the effect of an IAR-based navigation system in terms of cognitive map development. The findings from this research extend the existing knowledge about IAR-based navigation and further verify that AR technology has the potential to reduce human workload for cognitive tasks. The results also could support its more effective application in various scenarios that require assisted wayfinding and cognitive map training, such as emergency evacuation drills.